The use of new technologies in the work of Book Storage Department (BSD) - Kulikowski de Nałęcz, Artur; Nowak, Renata; Foremny, Andrzej (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article presents the scope of applicability new tools based on computer technologies in the work of Book Storage Department. It gives their significance and influence on book ordering and the use of electronic sources of information to verify bibliographical data of documents in cases of discrepancies between accession lists and catalog. Discussed is also the range of application of catalog modules and the circulation of VIRTUA integrated library system. The authors also describe the database of duplicate copies started in 2010: they depict its aim, methodology of creating a item record, as well as its present and future applicability.
Keywords: superfluous prints; automation; circulation; cataloging; library resources; duplicate copies